Experimental Flow Visualization of a NACA 4412 Airfoil Equipped with a 60° Forward Wingtip Fence in a Subsonic Wind Tunnel - Rasendriya, Firja Zahran; Suyatmo (SAINSTECH NUSANTARA, 2025)
Wingtip-induced three-dimensional flow accelerates boundary-layer separation and amplifies vortex-related losses, particularly at low Reynolds numbers. This study experimentally investigates the surface-flow characteristics of a NACA 4412 airfoil equipped with a 60° forward wingtip fence under subsonic conditions. Wind-tunnel experiments were conducted at a freestream velocity of 10 m/s (Re ≈ 2.3 × 10⁴) over angles of attack ranging from 0° to 17°. Oil-flow visualization and tuft visualization were employed to identify laminar–turbulent transition (Xt), separation (Xs), and reattachment (Xr) locations and to qualitatively assess near-surface flow stability. Compared with the baseline airfoil, the 60° forward wingtip fence systematically shifted separation downstream and delayed vortex development in the pre-stall regime. At 10°, the separation point moved from approximately 20 mm (baseline) to 30 mm, while reattachment shifted from 30 mm to 45 mm. Tuft observations indicate that significant vortex formation appeared earlier in the plain configuration (from 12°), whereas the fenced configuration maintained comparatively stable flow up to 12° and exhibited pronounced instability primarily at 15°–17°. The results demonstrate that a 60° forward wingtip fence enhances upper-surface flow stability and postpones separation onset at low Reynolds numbers, providing experimental guidance for compact wingtip-device optimization.